Development of Cloning Biotechnology Learning Media Based on Virtual Laboratory to Enhance High School Students’ Learning Motivation - Meylani, Nia; Fattahillah, Nuris; Hidayat, Ujang Syarip; Lyesmaya, Dyah (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
To evaluate the validity, practicality, and effectiveness of a cloning-based Virtual Laboratory in enhancing high school students’ learning motivation. Specifically, this study addresses: (1) the objectives of the research; (2) how the study was conducted; (3) the results obtained; and (4) the novelty of the work. This research employed a Research and Development (R2D2) approach consisting of definition, design–development, and dissemination phases. Media validation involved subject matter experts, instructional design experts, media experts, and biology teachers. Effectiveness was measured using the ARCS questionnaire (Attention, Relevance, Confidence, Satisfaction) and analyzed with a Paired Sample t-test. The media demonstrated very good validity (84.72–97.29%), high readability and practicality (85.20% and 90.69%, respectively), and positive student responses (86.62%). Students’ learning motivation increased significantly across all ARCS dimensions, with an average improvement of 0.77. This study addresses a gap in the application of Virtual Laboratories to the high school cloning topic a complex and abstract area rarely implemented due to limited laboratory facilities. The novelty lies in the development and validation of a cloning-specific Virtual Laboratory combined with motivation measurement using the ARCS model, offering an adaptive and effective solution to bridge the gap between curriculum demands and schools’ laboratory constraints.